Enhancing sustainability performance: Integrating green transformational leadership, green organizational culture, and total quality management - Utik Bidayati; Hendro Setyono; Tania Chusna Azzahra (Jurnal Fokus Manajemen Bisnis, 2026)
Modern organizations need to understand the drivers of sustainability to remain competitive. This study examines sustainable performance by considering the roles of green transformational leadership and green organizational culture, with total quality management acting as an intervening variable. This study involved 161 respondents from micro, small, and medium enterprises in the batik sector in Yogyakarta, Indonesia as the unit of analysis. Statistical analysis was conducted using Smart PLS 4.0. The results indicate that green organizational culture plays a significant role in strengthening both sustainable performance and total quality management. While no direct relationship is found between green transformational leadership and sustainable performance, this leadership style has been shown to support improvements in total quality management practices. The results show that total quality management enhances sustainable performance and serves as a mediating mechanism linking green transformational leadership and green organizational culture to sustainable outcomes. This suggests that sustainable performance is shaped not only by environmentally oriented values and leadership but also by the effectiveness of integrated quality practices. The results lend support to both the resource-based view and the natural resource-based view, emphasizing that organizational factors can be leveraged as strategic resources to enhance and sustain competitive advantage over time. In practice, this study recommends strengthening green culture and leadership by improving the implementation of total quality management, which supports sustainability.